Effects of wetting and drying cycles on the germination of nine species of the Chihuahuan Desert - Contreras Quiroz, Mariana del Rocío; Pando Moreno, Marisela; Flores, Joel; Jurado, Enrique (Sociedad Botánica de México, 2016)
Plants from drylands have developed strategies to germinate even in places where available humidity is sporadic with large periods of drought. Previous works determined germination of cacti species as a response to discontinuous humidity events (“seed hydration memory”). This study is aimed at assessing whether species of the Chihuahuan Desert show a seed hydration memory. Our hypothesis is that seeds of desert species can tolerate periods of dehydration after single or multiple hydration events and subsequently germinate more and faster. We evaluated nine species: Atriplex canescens, Cucurbita foetidissima, Echinocactus platyacanthus, Ferocactus pilosus, Lepidium virginicum, Lesquerella berlandieri, Nassella tenuissima, Sartwellia mexicana, and Yucca filifera, using four treatments: T1 = 24 hours hydration/5 days dehydration (HD), T2 = Three consecutive cycles of 24 hours hydration/5 days dehydration, T3 = 72 hours hydration/5 d dehydration, and T4 = Control. Echinocactus platyacanthus, N. tenuissima, F. pilosus, and L. virginicum showed higher germination with HD treatments than the control. Ferocactus pilosus and L. virginicum had the highest germination in T2, N. tenuissima in T3, E. platyacanthus in any HD treatment while Yucca filifera in the control and T2. Yucca filifera and F. pilosus had the lowest germination rate (t 50) in T2; E. platyacanthus in T1 and T2. The remaining species didn’t show differences in t 50 between treatments. These results indicate that at least some desert species germinate more and faster after single or multiple hydration-dehydration events showing the ability of those seeds to retain, during dehydration, the physiological changes produced from seed hydration.